Detrimental Effects and Prevention of Acidic Electrolytes on Oxygen Reduction Reaction Catalytic Performance of Heteroatom-Doped Graphene Catalysts - Ma, Jun; Gong, Lele; Shen, Yang; Sun, Defeng; Liu, Bowen; Zhang, Jing; Liu, Dong; Zhang, Lipeng; Xia, Zhenhai (Frontiers in Materials, 2019)
Heteroatom-doped carbon based catalysts have been demonstrated as one type of the most promising electrocatalysts to replace traditional noble metal catalyst, such as Pt for oxygen reduction reaction (ORR) in proton-exchange membrane fuel cells (PEMFCs). However, experimental results have shown that the carbon based catalysts exhibit inferior catalytic activities in acidic than that in alkaline mediums. As the catalytic mechanisms is unclear, there is no effective strategy to design and synthesize highly efficient carbon based catalysts working in acidic medium. In this work, the density functional theory (DFT) methods was applied to understand the inferior performance of doped graphene in acid. Our results show that the excellent performance of doped graphene is downgraded by protonation of dopants and the adsorption of acidic anions. The ORR overpotentials were calculated to be higher due to the protonation and the aggregation extent of acid anion on the graphene surface. To enhance the catalytic activities, the adverse effects of protonation and acid anion should be minimized as much as possible. These insights provide a direction to boost the catalytic efficiency and stability of metal-free carbon based catalysts for clean energy conversions and storages.